Book yourself solid the fastest, easiest, and most reliable system for getting more clients than you can handle even if you hate marketing and selling - Port, Michael 1970- (Wiley, 2011)
"Book Yourself Solid provides a true understanding of why self-promotion is a critical factor to success. It is this different and unique perspective that makes Book Yourself Solid so much more than an ordinary "how to" manual for getting more clients and raising a business profile. Michael helps the reader adopt this perspective and then provides the strategies, techniques, and skills necessary to get more clients and increase profits. Through verbal and written exercises, readers learn how to develop a strong marketing plan and brand image. In 2006, Michael published this book about marketing for the small business owner without addressing Facebook, LinkedIn or Twitter--which didn't even exist at the time. The 2nd edition of Book Yourself Solid will change all of that with brand new information, including: unique, personalized online marketing strategies for service professionals new SEO rules to optimize search engine listings and traffic solid social media exposure and dominance strategies."--
Includes bibliographical references and index. - Print version record
Keywords: Selling; Marketing; Strategic planning; Vente; Planification stratégique; selling; marketing; BUSINESS & ECONOMICS; Marketing; General; BUSINESS & ECONOMICS; Distribution